Enhancement of Ion Pairing of Sr(II) and Ba(II) Salts by a Tritopic Ion‐Pair Receptor in Solution - Kutus, Bence (Chemphyschem, 2020)
Tritopic ion‐pair receptors can bind bivalent salts in solution; yet, these salts have a tendency to form ion‐pairs even in the absence of receptors. The extent to which such receptors can enhance ion pairing has however remained elusive. Here, we study ion pairing of M(2+) (Ba(2+), Sr(2+)) and X(−) (I(−), ClO(4) (−)) in acetonitrile with and without a dichlorooxacalix[2]arene[2]triazine‐related receptor containing a pentaethylene‐glycol moiety. We find marked ion association already in receptor‐free solutions. When present, most of the MX(+) ion‐pairs are bound to the receptor and the overall degree of ion association is enhanced due to coordinative, hydrogen‐bonding, and anion‐π interactions. The receptor shows higher selectivity for iodides but also stabilizes perchlorates, despite the latter are often considered as weakly coordinating anions. Our results show that ion‐pair binding is strongly correlated to ion pairing in these solutions, thereby highlighting the importance of taking ion association in organic solvents into account.